Effectiveness of optimal health program in improving self-efficacy in type 2 diabetes mellitus primary care patients in Putrajaya, Malaysia - Suhaimi, Aida Farhana (2021)
Diabetes is seeing an increasing trend globally and locally. Despite advances in medical and healthcare services, Malaysia is still witnessing increased prevalence of disability, co-morbidity, medical complications and poor well-being amongst patients with diabetes. The current approach in diabetes management that is predominantly education and medical focus is no longer adequate to address the complexity of diabetes. Self-efficacy has been found to be fundamental in the process of effective diabetes self-management. The Optimal Health Program (OHP) is a self-management intervention that is wellness-based, person-centred, driven by self-efficacy theory and aimed towards patient empowerment. This study aims to examine the effectiveness of the OHP in improving self-efficacy in Type 2 Diabetes Mellitus (T2DM) patients attending the primary healthcare clinics in Putrajaya. This study is a single blind randomized controlled trial. This study recruited patients (n = 127) diagnosed with T2DM from primary healthcare clinics in Putrajaya. Participants were randomised to either OHP plus treatment-as-usual (OHP plus TAU) or treatment-as usual alone (TAU). The 2-hour weekly sessions conducted over 5 consecutive weeks (i.e., up to Week 5), and 2-hour session at three months post fifth session (i.e., Week 18) were facilitated by trained mental health practitioners and diabetes educators. Primary outcomes were self-efficacy (psychosocial self-efficacy and diabetes management self-efficacy), while secondary outcomes were mental health (depression, anxiety, diabetes-related distress and wellbeing), self-care behaviours and glycaemic control (HbA1c). These outcome measures were assessed at baseline, at Week 5, Week 18 and Week 30. The intention-to-treat analyses were performed with missing values imputed using the LOCF approach. The study’s findings provided evidence on the effectiveness of OHP plus TAU when compared to TAU alone in improving self-efficacy (F (2,122) = 8.28, p < 0.001, partial η² = 0.12), with effect observed at Week 5 and Week 18. Across time, OHP plus TAU improved both psychosocial self-efficacy (F (3, 122) = 31.74, p < 0.001) and diabetes management self-efficacy (F (3,122) = 13.62, p < 0.001). However, this study did not find significant difference between OHP plus TAU and TAU alone for self-care behaviours and mental health outcomes. Nonetheless, OHP plus TAU showed improvement in self-care behaviours and mental health outcomes over time. This study failed to provide any evidence on the effectiveness of OHP plus TAU in improving glycaemic control. This study found OHP to be effective as an add-on self-management intervention to the current treatment of T2DM patients in the primary healthcare clinics in improving psychosocial and diabetes management self-efficacy. Beneficial effect on mental health outcomes were limited whilst self-care behaviours yielded a more short-term beneficial effect. There was no beneficial effect on glycaemic control found. Future studies that assess the sustainability of the program at long term and incorporate ongoing support, with frequent contact between sessions and in a longer duration would be beneficial.